A method of distributed virtual cluster formation in system of several clusters connected through a global network - Кулаков, Ю. А.; Алєнін, О. И. (Problems of Informatization and Control, 2009)
The problems of consolidation of several cluster systems in a uniform computing resource are considered. The review of methods of resource allocation in systems with different networks structure between clusters is made. The mathematical model of task solving time and cost in a system of clusters connected through a global network is given. The modified method of distributed virtual cluster formation is offered